ISH NIA OS-01 THE microRNA miR-19a-3p BINDS TO A POLYMORPHISM IN THE GENE FOR THE NORADRENALINE TRANSPORTER AND MAY INCREASE THE RISK OF CARDIOVASCULAR AND PSYCHIATRIC DISEASE. (September 2016) - Marques, Francine; Eikelis, Nina; Bayles, Richard; Straznicky, Nora; Hering, Dagmara; Esler, Murray; Head, Geoffrey; Schlaich, Markus; Lambert, Gavin
Abstract : Objective: Noradrenaline released from sympathetic nerves is removed from the neuroeffector junction via the action of the noradrenaline transporter (NET). NET impairment is evident in several clinically important conditions including essential hypertension, major depressive disorder, panic disorder and the postural orthostatic tachycardia syndrome. Only in rare instances, however, do coding single nucleotide polymorphisms (SNPs) seem to account for a defect in NET. The aim of this study was to determine whether rs7194256 (C/T), a SNP in the 3' untranslated region (UTR) of the NET gene, is associated with diseases associated with NET dysfunction, and to elucidate the mechanism involved. Design and Method: We genotyped by real-time PCR (qPCR) the rs7194256 SNP in a cohort of 55 European-descendent healthy controls and 122 patients (including 44 hypertensives), and validated the results in a larger cohort of 238 controls and 258 cases (124 hypertensives). Bioinformatic analyses identified microRNAs that could bind to the sequence created by the presence of the T allele, and luciferase assays validated it. Results: Cases had significantly higher prevalence of the T allele, arterial noradrenaline, depression and anxiety scores, clinical and ambulatory systolic and diastolic blood pressures, and larger left ventricular mass index (all P < 0.05). Carriers of the T allele also had higher arterial noradrenaline (P = 0.002) and 3, 4-dihydroxyphenylglycol (the intraneuronal metabolite of noradrenaline, P = 0.016). Bioinformatic analyses showed that the T allele created a binding site for the microRNA miR-19a-3p, and luciferase assays validated that this microRNA binds preferentially to the T allele (P < 0.0001). Conclusions: The T allele of the rs7194256 SNP in the 3'UTR of the NET gene is associated with diseases associated with NET dysfunction, including hypertension. This might be explained by the creation of a binding site for the microRNA miR-19a-3p. A defect in NET function may potentiate the sympathetic neurochemical signal, predisposing individuals to increased risk of cardiovascular disease development.